DEVELOPING STUDENTS SPEAKING WORKSHEET USING VAK LEARNING MODEL AT ELEVENTH GRADE STUDENTS OF MAN 2 KOTA BENGKULU - Muhammad Reza Madiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking is a fundamental skill in English language learning that requires active, contextual, and student-centered instructional support. However, speaking instruction at the senior high school level often relies heavily on textbooks and teacher-centered methods, which do not adequately accommodate students’ diverse learning styles. This study aims to identify the speaking material needs of eleventh-grade students and to develop a speaking worksheet based on the VAK (Visual, Auditory, Kinesthetic) learning model at MAN 2 Kota Bengkulu. This research employed a mixed-method approach, combining qualitative and quantitative methods. Data were collected through interviews with English teachers, classroom observations, student questionnaires, and document analysis. The needs analysis results revealed that students require interactive, contextual, and varied speaking materials that support visual, auditory, and kinesthetic learning preferences. Most students showed a tendency toward kinesthetic and visual learning styles, indicating the need for materials that involve active practice such as role plays, discussions, simulations, and visual aids. Based on these findings, a VAK-based speaking worksheet was developed to provide balanced activities that integrate visual stimuli, auditory interaction, and kinesthetic engagement. The developed worksheet is expected to enhance students’ speaking confidence, fluency, and participation by providing more opportunities for meaningful oral practice. This study contributes to the development of adaptive speaking instructional materials and offers practical implications for English teachers in designing learning resources that accommodate diverse learning styles.